2014
DOI: 10.5114/pwki.2014.46771
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic conditioning in percutaneous coronary intervention: a meta-analysis of randomised trials

Abstract: IntroductionIt remains uncertain whether remote ischaemic conditioning (RIC) using cycles of limb ischaemia-reperfusion as a conditioning stimulus benefits patients undergoing percutaneous coronary intervention (PCI).AimWe performed a meta-analysis toassessthe effect of RIC in PCI.Material and methodsThe PubMed, EMBASE, Web of Science, and CENTRAL databases were searched for randomised controlled trials (RCTs) comparing RIC with controls. The treatment effects were measured as a pooled odds ratio (OR), standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The neurons of the spinal cord are better prepared for upcoming ischemia after RIPC, which might be explained by the above-mentioned mechanisms, although they have been studied more extensively in the context of myocardial ischemia. 18,[25][26][27][28] In an experimental model by Donato et al, 26 sectioning of spinal cord extinguished the protective effect of RIPC in the myocardium, indicating the involvement of neuronal afferent signaling. Therefore, we took extra precautions to not damage the femoral nerve while operating on the right femoral vessels.…”
Section: Discussionmentioning
confidence: 97%
“…The neurons of the spinal cord are better prepared for upcoming ischemia after RIPC, which might be explained by the above-mentioned mechanisms, although they have been studied more extensively in the context of myocardial ischemia. 18,[25][26][27][28] In an experimental model by Donato et al, 26 sectioning of spinal cord extinguished the protective effect of RIPC in the myocardium, indicating the involvement of neuronal afferent signaling. Therefore, we took extra precautions to not damage the femoral nerve while operating on the right femoral vessels.…”
Section: Discussionmentioning
confidence: 97%
“…Many clinical observations have found that increased levels of myocardial injury markers, such as troponin T, troponin I, and CK-MB, are associated with adverse long-term prognosis after elective percutaneous coronary intervention [ 41 , 46 , 47 ]. In the meta-analysis by Niu et al [ 48 ], it was found that RIPC can reduce myocardial injury markers after PCI release; this protective effect was more obvious in STEMI patients, while in the elective PCI patients, RIPC cannot reduce myocardial injury markers, and the heterogeneity of the included studies was larger. To our knowledge, this is the first meta-analysis to explore whether RIPC could reduce the release of myocardial markers after PCI in patients with elective PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the studies of classical preconditioning, Liu et al demonstrated that late RIPC also had beneficial effects on patients undergoing elective PCI [29]. Although there is heterogeneity in RIPC protocols, meta-analyses of the major RIPC studies in elective PCI indicated that ischemic preconditioning had beneficial effects on post-PCI myocardial injury [3133]. …”
Section: Discussionmentioning
confidence: 99%